Efecto antimicrobiano de tres cementos endodónticos sobre porphyromona gingivalis atcc 33277 - Grace Viviana, Santos Miranda (2021)
ABSTRACT The aim of this research was to evaluate the antimicrobial effect of three endodontic cements on the strain of Porphyromona gingivalis ATCC 33277 by means of an in vitro study. A quasi-experimental study with a mixed design and a cross-sectional approach was carried out. The data collection technique was the observation, and the instrument was the BMI laboratory logbook. The study population was made up by 30 samples, 10 for each endodontic cement evaluated (Bioroot, Adseal, Sealapex). In this study, the porphyromona gingivalis was cultured in strict anaerobic media exposed in the incubator at 37ºC and the diameter of the inhibition halos was subsequently recorded at 24 and 48 hours. The observed results indicated that the endodontic cement with the best antimicrobial activity was the Bioroot with a median of 21.78 mm and a standard deviation of ±1.31 in all the analyzed samples, according to the Duraffourd’s scale, it is extremely sensitive. In this way, from the results obtained in the study and statistically significant comparisons, it is established that the most powerful antimicrobial activity against Porphyromona gingivalis was the one presented by Bioroot (p=0.084), followed by Adseal and finally Sealapex with a minimum activity. Keywords: Porphyromona gingivalis, Endodontics, Endodontic cements.